Juridical Analysis of Criminal Liability for the Crime of Impaired Marriage in the Criminal Code (Study Decision Number 17/ Pid.B/ 202/ PN. Blg) - Mohammad Eka Putra; Utary Maharany Barus; Empindonta Ramadhaan Tarigan (Universitas Efarina, 2025)
Criminal liability for the crime of obstructing marriage is regulated in article 279 of the Criminal Code which states that anyone who enters into a marriage even though he knows that his existing marriage or marriages are a legal obstacle to that, or whoever enters into a marriage even though he knows that the marriage or marriages of another party become Obstruction to do so is punishable by a maximum imprisonment of five years. There is an example of a case regarding an obstructed marriage as contained in Decision Number 17/Pid.B/2021/PN.Blg, the defendant's actions are regulated and punishable by crime in Article 279 paragraph (1) 1 of the Criminal Code. 1. Declare that the defendant, Estomihi Siahaan, as mentioned above, has been legally and convincingly proven guilty of committing the crime of